2019
DOI: 10.1021/acs.joc.8b03175
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Radical C–C Bond Cleavage and [4+1] Annulation Cascade of Cycloketone Oxime Esters with Enaminothiones

Abstract: Carbon–carbon bond formation is among the most important reactions in organic synthesis. Reconstruction of a carbon–carbon bond through ring-opening C–C bond cleavage of a strained carbocycle usually occurs via a thermodynamically preferable pathway. However, carbon–carbon bond formation through thermodynamically less favorable C–C bond cleavage has seldom been documented. Herein, we disclose an unusual C–C bond cleavage of cycloketone oxime esters for [4+1] annulation. Under anaerobic copper­(I) catalysis, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…We recently found that alkylthio‐substituted enaminones and enaminothiones, that is, α‐oxo (thioxo) ketene N,S‐acetals, could undergo carbene insertion reactions to establish O‐ and S‐heterocycles under copper(II) catalysis or metal‐free conditions (Scheme a), and cycloketone oxime esters were also used as the C1 building blocks to react with enaminothiones in the presence of a copper(I) catalyst to give thiophene derivatives (Scheme b) . Thus, we envisioned that sulfur ylides might also act as the suitable C1 building blocks to react with alkylthio‐substituted enaminones and enaminothiones to execute [4+1] annulation to afford multisubstituted furan and thiophene derivatives (Scheme c).…”
Section: Figurementioning
confidence: 99%
“…We recently found that alkylthio‐substituted enaminones and enaminothiones, that is, α‐oxo (thioxo) ketene N,S‐acetals, could undergo carbene insertion reactions to establish O‐ and S‐heterocycles under copper(II) catalysis or metal‐free conditions (Scheme a), and cycloketone oxime esters were also used as the C1 building blocks to react with enaminothiones in the presence of a copper(I) catalyst to give thiophene derivatives (Scheme b) . Thus, we envisioned that sulfur ylides might also act as the suitable C1 building blocks to react with alkylthio‐substituted enaminones and enaminothiones to execute [4+1] annulation to afford multisubstituted furan and thiophene derivatives (Scheme c).…”
Section: Figurementioning
confidence: 99%
“…Yu and co-workers reported a copper-catalyzed [4+1] annulation of cycloketone oxime esters 12 with -thioxo ketene N,S-acetals 134 to access 2-cyanoalkyl-3-aminothiophene derivatives 135 (Scheme 35). 53 The five-membered S-heterocycle was constructed through the abstraction of hydrogen adjacent to the S-atom in intermediate 137 by the carboxylate anion followed by addition to the in situ generated iminium ion. This is the first example with cycloketone oxime esters as the C1 building blocks in an annulation reaction.…”
Section: Scheme 34 Copper-catalyzed Tandem Ring-opening/cyclization Fmentioning
confidence: 99%
“…In 2019, Yu and co‐workers demonstrated an efficient copper(I)‐catalyzed [4+1] annulation of cycloketone oxime esters with enaminothiones 90 for the synthesis of 2‐cyanoalkyl‐3‐aminothiophene derivatives 91 , where cycloketone oximes esters served as C1 building blocks (Scheme 31). [43] With CuCl as the catalyst, various substituted enaminothiones were treated with symmetrical and asymmetrical cycloketone oxime esters to afford cyanoalkylated thiophenes in moderate to good yields. Interestingly, an unusual and thermodynamically less favorable ring cleavage of 2‐substituted cycloketone oximes was observed.…”
Section: Transition‐metal Catalyzed Cross‐coupling Reactionsmentioning
confidence: 99%